Mathematics Learning Achievement of School Students through Virtual and Face to Face Mode of Learning - Dhakal , Prem Kumari; Khanal , Bishnu (Academic Journal of Mathematics Education, 2025)
The main objective of this paper is to examine the difference between mathematics learning achievement of school students through virtual and face to face mode of learning. This quasi-experimental study was conducted in two similar institutional schools of Birendranagar municipality Surkhet. All the students of grade nine from sample schools were the participants of this study, however the intervention and comparison groups were made similar on the basis of number, inclusiveness, grade of mathematics in Basic Level Examination, first-terminal examination and pre-test. Pre-test and post-test were conducted using the similar parallel sets of test items that were finalized by piloting and analyzing the items. SPSS-20 was used as the tool of data analysis. The result revealed that learners through virtual mode of leaning performed better than traditional face to face mode of learning mathematics and the study suggests that virtual mode of learning can be an alternative learning approach in school level to increase the mathematics achievement.